Neurocognitive and psychiatric symptoms following infection with COVID-19: Evidence from laboratory and population studies - Peter A. Hall; Hasan Ayaz; Gang Meng; Anna Hudson; Mohammad N. Sakib; Anne C.K. Quah; Thomas K. Agar; Jessica A. Lee; Christian Boudreau; Geoffrey T. Fong (Brain, Behavior, & Immunity - Health, 2023)
Objective: The objective of the current investigation was to examine associations between symptomatic COVID-19 history, neurocognitive function, and psychiatric symptoms using cognitive task performance, functional brain imaging, and a prospective population survey. Methods: Study 1 was a laboratory study conducted between 3 May 2022 and 16 Nov 2022 involving 120 fully vaccinated community dwelling adults between 18 and 84 years of age (Mage = 31.96 (SD = 20.71), 63.3% female). In this cross-sectional study we examined the association between symptomatic COVID-19 infection history and performance on three computer tasks assessing cognitive function (Flanker interference, delay discounting and simple reaction time) and measured oxygen saturation within the prefrontal cortex using functional near infrared spectroscopy (fNIRS). Study 2 was a 2-wave population survey undertaken between 28 September 2021 and 21 March 2022, examining the prospective relationship between symptomatic COVID-19 and self-reported symptoms of cognitive dysfunction, depressive symptoms, anxiety symptoms, and agitation at 6-month follow up. The sample (N = 2,002, Mage = 37.0, SD = 10.4; 60.8% female) was collected using a quota process to ensure equal numbers of vaccinated and unvaccinated individuals. Structural equation modelling with latent variables was performed on the population-level data, evaluating the fit of the proposed mediational model of symptomatic COVID-19 to psychiatric symptoms through cognitive dysfunction. Results: Findings from Study 1 revealed significant effects of symptomatic COVID-19 history on Flanker interference and delay discounting. Effects on flanker performance were significantly stronger among older adult women (effect: 9.603, SE = 4.452, t = 2.157, p = .033), and were accompanied by task-related changes cerebral oxygenation at the right superior frontal gyrus (F (1, 143.1) = 4.729, p = .031). Additionally, those with a symptomatic COVID-19 infection history showed evidence of amplified delay discounting (coefficient = 0.4554, SE = 0.2208, t = 2.0629, p = .041). In Study 2, baseline symptomatic COVID-19 history was associated with self-reported cognitive dysfunction and a latent variable reflecting psychiatric symptoms of anxiety, depression and agitation at follow-up. Mediational analyses revealed evidence of cognitive mediation of clinically significant psychiatric outcomes: depression (indirect effect = 0.077, SE = 0.026, p = .003) and generalized anxiety (indirect effect = 0.060, SE = 0.021, p = .004). Conclusions: Converging findings from laboratory and population survey data support the conclusion that symptomatic COVID-19 infection is associated with task-related, functional imaging and self-reported indices of cognitive dysfunction as well as psychiatric symptoms. In some cases, these findings appear to be more amplified among women than men, and among older women than younger.